Medieval spawn and witchblade (2018), volume 1 ebook - holguin, Brian (Medieval Spawn and Witchblade (2018), 2018)
SPAWN AND WITCHBLADE TOGETHER AGAIN FOR THE FIRST TIME IN DECADES! An ancient evil sweeps the world, destroying and corrupting everything in its path. When a knight SPAWNs from out of the shadows to save all, he is touted as their benevolent king of old, miraculously returned. But is he their savior, or their destroyer? With an evil queen, a knight in search of his past, and a young girl with an ancient weapon that could destroy them all, the world is in more danger than ever. NOTE: Augmented reality covers and interiors for both iOS and Android devices. Collects MEDIEVAL SPAWN / WITCHBLADE #1-4. Author: Brian Holguin. Illustrator: Brian Haberlin, Brian Haberlin . 2018 Todd McFarlane Productions, Top Cow Productions, inc.